Advances in Modelling COVID-19 in Animals - Nickl, Petr; Raishbrook, Miles Joseph; Syding, Linn Amanda; Sedlacek, Radislav (Frontiers in Drug Discovery, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) is a positive-sense-single stranded RNA virus and the cause of the coronavirus disease 2019 (COVID-19). The World Health Organisation has confirmed over 250 million cases with over 5.1 million deaths as a result of this pandemic since December 2019. A global outbreak of such intensity and perseverance is due to the novelty of SARS-CoV2 virus, meaning humans lack any pre-existing immunity to the virus. Humanised animal models, from rodents to primates, simulating SARS-CoV2 transmission, cell entry and immune defence in humans have already been crucial to boost understanding of its molecular mechanisms of infection, reveal at-risk populations, and study the pathophysiology in vivo. Focus is now turning towards using this knowledge to create effective vaccines and therapeutic agents, as well as optimise their safety for translatable use in humans. SARS-CoV2 possesses remarkable adaptability and rapid mutagenic capabilities thus exploiting innovative animal models will be pivotal to outmanoeuvre it during this pandemic. In this review, we summarise all generated SARS-CoV2-related animal models to date, evaluate their suitability for COVID-19 research, and address the current and future state of the importance of animal models in this field.